Perbandingan Hasil Immunocromatography Merk A dan B Pada Pemeriksaan Hepatitis B Surface Antigen (HBsAg) - Hafiz Mukaromah; Budi Santosa; Meutia Srikandi Fitria (MES Bogor, 2024)
Hepatitis is an infectious disease that arises from infection with the hepatitis B virus (VHB), a member of the HBV family that can cause acute or chronic inflammation of the liver, which in some cases can progress to cirrhosis or liver cancer. HBsAg is a type of antigen contained in the membrane of the hepatitis B virus and can be detected in infected body fluids. Immunochromatography is a qualitative analysis method that binds antigen-antibodies in the form of a rapid test that detects the presence of targets in the sample without the use of special tools. The type of study was conducted using cross sectional with serum samples from 38 respondents who were examined for HBs antigen using the Immunocromatography method brand A and B. The results showed a negative result of 100%. After the analysis data using the Mann Whitney statistical test, the asymp.sig value (p-value) obtained was 1.803 which means >0.05, there was no significant comparison between brand A (wondfo) and brand B (monotest) diagnosing HbsAg). It was concluded that there was no significant comparison in the HBsAg examination using Immunocromatography brand A and B